Optimized MaxEnt analysis revealing the change of potential distribution area of Lygodium japonicum in China driven by global warming - Shan, Yuxin; Shen, Hongjian; Huang, Ling; Hamezah, Hamizah Shahirah; Han, Rongchun; Ren, Xia; Zhang, Chunhong; Tong, Xiaohui (Frontiers in Plant Science, 2025)
Lygodium japonicum is a valuable medicinal plant with increasing demand in China, yet large-scale cultivation remains limited, relying heavily on wild populations. As climate change accelerates, its potential distribution is expected to shift, affecting suitable growth areas. Despite its medicinal importance, research on its adaptability and future habitat changes is limited. This study used an optimized MaxEnt ecological niche model and Geographic Information System (GIS) to predict the potential suitable habitats of L. japonicum under current and future climate conditions (2041-2060 and 2061-2080) across three greenhouse gas emission scenarios (SSP126, SSP245, SSP585). Results show that under current climatic conditions, the potential habitat of L. japonicum spans approximately 216.31 × 104 km², with high suitability areas concentrated in southern and eastern China. In future climate scenarios, While the total suitable habitat area remains stable, the area of high suitability is significantly reduced. Specifically, under the SSP126 scenario, high suitability areas are projected to decrease by 44.1% during 2041-2060. The centroid of high suitability areas is expected to shift northward, though a localized southward shift is observed under the SSP126 scenario. Key environmental factors influencing the species’ distribution include temperature seasonality (bio4), May precipitation (prec5), and mean diurnal temperature range (bio2). These findings highlight the potential impacts of climate change on L. japonicum’s distribution and are crucial for the conservation and sustainable utilization of the species in China, particularly under changing climatic conditions.